Stigmatization of people who inject drugs (PWID) by pharmacists in Tajikistan: sociocultural context and implications for a pharmacy-based prevention approach - Umedjon Ibragimov; Hannah L. Cooper; Regine Haardörfer; Kristin L. Dunkle; William A. Zule; Frank Y. Wong (BMC, 2017)
Abstract Background Pharmacies are an important source of sterile syringes for people who inject drugs (PWID) in Tajikistan who are under high risk of HIV and hepatitis C virus. Accessibility of sterile syringes at pharmacies without prescription may depend on pharmacists' attitudes towards PWID. This qualitative inquiry examines meanings and processes of stigmatization of PWID among pharmacists and pharmacy students in Tajikistan. Methods We conducted semi-structured interviews with 19 pharmacists and 9 students (N = 28) in the cities of Dushanbe and Kulob, Tajikistan. The interview topics included personal attitudes towards drug use and PWID, encounters with PWID, awareness and beliefs related to drug dependence and HIV, and attitudes and practices related to providing syringes to PWID. Interview transcripts were analysed using thematic analysis methods. Results The main themes included the significance of religion in defining attitudes towards drug use, labelling of PWID, negative stereotypes (PWID are prone to crime, violence, and irrational aggression; inflict harm to families and society; are able to control drug use), emotions triggered by PWID (fear, sympathy) and discrimination against PWID (rejection, isolation, ostracism, limiting resources to PWID). The religious ban on drug use and pharmacists' moral and legal responsibility for the consequences of drug use were frequently mentioned as reasons for rejecting syringe sales. Still, many participants acknowledged the need for distributing syringes to PWID to prevent HIV. Conclusions Stigma against PWID in Tajikistan plays an important role in shaping pharmacists' attitudes towards provision of services to this population. Local sociocultural context, in particular religious beliefs and social conservatism, may facilitate stigmatizing beliefs.